Analisis Faktor Risiko Kejadian Hipertensi di Puskesmas Lubuk Batang Wilayah Kerja Dinas Kesehatan Kabupaten OKU Tahun 2021 - Evita Puryanti; Erma Gustina; Yusnilasari (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Hypertension is a disease that is still a concern of all circles of society, because of the impact that can be caused by hypertension in the short and long term. The OKU District Health Office showed that hypertension was the 10th largest disease and the highest number of diseases was 20,000 cases. The purpose of this study was to analyze the risk factors associated with the incidence of hypertension. The study was carried out on April 1, 2021 to June 1, 2021 at the Lubuk Batang Health Center in the Work Area of ??the OKU District Health Office in 2021. The research design will use a quantitative method with a cross sectional design. The sample of this study amounted to 100 people who were patients who came for treatment at the Lubuk Batang Health Center at the time of the study. The results of the study on bivariate analysis obtained p values ??for age (0.038), gender (0.153), occupation (0.200), exercise (1,000), family history of disease (1,000), smoking (0.582). In the multivariate analysis, the age variable was obtained with a p value of 0.188. There is a significant relationship between age and the incidence of hypertension and there is no relationship between gender, occupation, exercise and family disease with the incidence of hypertension.